The Influence of Culture on Early Childhood Education Curriculum in the UAE. (June 2022) - Alhosani, Najwa
Purpose: This article provides an overview of how childhood curriculum in the United Arab Emirates (UAE) is designed to serve cultural values. Design/Approach/Methods: The framework of kindergarten curriculum adopts the uniqueness of children laying the foundation for their cultural identity. This paper provides a description of how this is achieved through a case study of the kindergarten curriculum in the UAE. Findings: The core elements of Emirati culture are delivered in the early childhood education (ECE) curriculum, which is influenced by global practices. Islamic studies is a key component in the Emirati kindergarten curriculum, which is designed to help children practice principles of religion, with the main Islamic values of gratitude and charity as aspects that are deeply embedded. Similarly, through social studies, children learn about Emirati heritage and culture. In addition to exposure to world communities, the learning experience engages children in authentic stories that relate to their personal lives, families, and community to build national awareness. Originality/Value: This paper sheds light on ECE in the UAE. Although the topic is of interest to UAE policymakers and educators and the global audience interested in UAE education, there is no study to the researcher's best knowledge that has examined the influence of the UAE culture on ECE curriculum.